Tumors around the ankle: a reconstructive challenge - Shanmugam, Subbiah; Vijayalakshmi, G. (International Journal of Research in Orthopaedics, 2024)
Tumors around the ankle can be either bone or soft tissue sarcomas. The aggressive nature of these tumors and the complex anatomy of the ankle mortice make for a challenging reconstructive ladder. We have explored four different histological tumors which required tailor made resection and reconstruction. All our patients had reasonably good functional outcomes.